Encrypting messages with artificial bacterial receptors - Kishore Prasad, Pragati; Lahav-Mankovski, Naama; Motiei, Leila; Margulies, David (Beilstein Journal of Organic Chemistry, 2020)
A method for encrypting messages using engineered bacteria and different fluorescently labeled synthetic receptors is described. We show that the binding of DNA-based artificial receptors to E. coli expressing His-tagged outer membrane protein C (His-OmpC) induces a Förster resonance energy transfer (FRET) between the dyes, which results in the generation of a unique fluorescence fingerprint. Because the bacteria continuously divide, the emission pattern generated by the modified bacteria dynamically changes, enabling the system to produce encryption keys that change with time. Thus, this development indicates the potential contribution of live-cell-based encryption systems to the emerging area of information protection at the molecular level.
Keywords: artificial receptors; cell surface modification; fluorescent probes; molecular cryptography

(untitled) - Zelikin, A. N.; Städler, B. (Small, 2020)

(untitled) - Lahav-Mankovski, N.; Prasad, P. K.; Oppenheimer-Low, N.; Raviv, G.; Dadosh, T.; Unger, T.; Salame, T. M.; Motiei, L.; Margulies, D. (Nat. Commun., 2020)

(untitled) - Nissinkorn, Y.; Lahav-Mankovski, N.; Rabinkov, A.; Albeck, S.; Motiei, L.; Margulies, D. (Chem. – Eur. J., 2015)

(untitled) - Rout, B.; Milko, P.; Iron, M. A.; Motiei, L.; Margulies, D. (J. Am. Chem. Soc., 2013)

(untitled) - Sarkar, T.; Selvakumar, K.; Motiei, L.; Margulies, D. (Nat. Commun., 2016)

(untitled) - Lustgarten, O.; Carmieli, R.; Motiei, L.; Margulies, D. (Angew. Chem., Int. Ed., 2019)

(untitled) - Lustgarten, O.; Motiei, L.; Margulies, D. (ChemPhysChem, 2017)

(untitled) - Andréasson, J.; Pischel, U. (Chem. Soc. Rev., 2018)

(untitled) - Margulies, D.; Felder, C. E.; Melman, G.; Shanzer, A. (J. Am. Chem. Soc., 2007)

(untitled) - Strack, G.; Ornatska, M.; Pita, M.; Katz, E. (J. Am. Chem. Soc., 2008)

(untitled) - Andréasson, J.; Straight, S. D.; Moore, T. A.; Moore, A. L.; Gust, D. (Chem. – Eur. J., 2009)

(untitled) - Carvalho, C. P.; Domínguez, Z.; Da Silva, J. P.; Pischel, U. (Chem. Commun., 2015)

(untitled) - Chen, J.; Zhou, S.; Wen, J. (Angew. Chem., Int. Ed., 2015)

(untitled) - La Clair, J. J. (Chem. Commun., 2018)

(untitled) - Arcadia, C. E.; Kennedy, E.; Geiser, J.; Dombroski, A.; Oakley, K.; Chen, S.-L.; Sprague, L.; Ozmen, M.; Sello, J.; Weber, P. M.; Reda, S.; Rose, C.; et al. (Nat. Commun., 2020)

(untitled) - Qin, M.; Xu, Y.; Gao, H.; Han, G.; Cao, R.; Guo, P.; Feng, W.; Chen, L. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - McGoldrick, L. K.; Weiss, E. A.; Halámek, J. (ACS Synth. Biol., 2019)

(untitled) - Hsu, C.-W.; Sauvée, C.; Sundén, H.; Andréasson, J. (Chem. Sci., 2018)

(untitled) - Boukis, A. C.; Reiter, K.; Frölich, M.; Hofheinz, D.; Meier, M. A. R. (Nat. Commun., 2018)

(untitled) - Ling, J.; Daly, B.; Silverson, V. A. D.; de Silva, A. P. (Chem. Commun., 2015)

(untitled) - Andréasson, J.; Pischel, U. (Chem. Soc. Rev., 2015)

(untitled) - Erbas-Cakmak, S.; Kolemen, S.; Sedgwick, A. C.; Gunnlaugsson, T.; James, T. D.; Yoon, J.; Akkaya, E. U. (Chem. Soc. Rev., 2018)

(untitled) - Yao, C.-Y.; Lin, H.-Y.; Crory, H. S. N.; de Silva, A. P. (Mol. Syst. Des. Eng., 2020)

(untitled) - Pode, Z.; Peri-Naor, R.; Georgeson, J. M.; Ilani, T.; Kiss, V.; Unger, T.; Markus, B.; Barr, H. M.; Motiei, L.; Margulies, D. (Nat. Nanotechnol., 2017)

(untitled) - Rout, B.; Unger, L.; Armony, G.; Iron, M. A.; Margulies, D. (Angew. Chem., Int. Ed., 2012)

(untitled) - Hatai, J.; Motiei, L.; Margulies, D. (J. Am. Chem. Soc., 2017)

(untitled) - Peri-Naor, R.; Pode, Z.; Lahav-Mankovski, N.; Rabinkov, A.; Motiei, L.; Margulies, D. (J. Am. Chem. Soc., 2020)